SEA WATER & COASTAL SOIL ANALYSIS FROM SELECTED COSTAL AREAS OF BHAVNAGAR DISTRICT, GUJARAT, INDIA (International Association of Biologicals and Computational Digest, 2022)
.In India, Gujarat is the only State having the largest coastal area spread around 1600 km. Bhavnagar is developed on the gulf of Khambhat; with coastal areas such as Ghogha, Kuda, Koliyak, Hathab, Mithiviradi, Zanzmer, Gopnath. The Quality of Sea Water depends on the coastal diversity about soil quality, due to that it also affects the diversity of plants and animals of the coastal region. The sea water analysis is performed for parameters such as pH, Temperature, Electrical Conductivity, Salinity, Total Dissolve Soild, Acidity, Alkalinity, Chloride, Total Hardness, Ca+2, Mg+2, Dissolve Oxygen, Biological Oxygen Demand, Chemical Oxygen Demand and soil from coastal area also subjected for soil analysis parameter such as pH, Temperature, Electrical Conductivity, Salinity, Chloride, Ca+2, Mg+2, Soli texture, Soil moisture, Soil porosity, Soil buffering capacity, Water holding Capacity, and Organic Carbon. It is making the impact on our finding gives us the knowledge of Seawater and coastal soil richness and diversity at a particular location; such as sandy, rocky and muddy. The coastal area affects the diversity of plants such as xerophytes and halophytes, which is dependent on the quality of the coast. Due to that, the analysis result gives us a beautiful scenario for habitat impact on seawater and coastal / tidal region soil.
Keywords: Qualitative Analysis, Seawater, Coastal area Soil, Abiotic factor